2020
DOI: 10.1371/journal.pone.0227243
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide identification of novel circular RNAs in soybean in response to low-phosphorus stress

Abstract: Low-phosphorus (LP) stress is a major factor limiting the growth and yield of soybean. Circular RNAs (circRNAs) are novel noncoding RNAs that play a crucial role in plant responses to abiotic stress. However, how LP stress mediates the biogenesis of circRNAs in soybean remains unclear. Here, to explore the response mechanisms of circRNAs to LP stress, the roots of two representative soybean genotypes with different P-use efficiency, Bogao (a LPsensitive genotype) and Nannong 94156 (a LP-tolerant genotype), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
6
30
0
Order By: Relevance
“…2b and Fig. S1, the number of DE lncRNAs under LP stress in Bogao is more than that in NN94156, indicating that the Bogao is more sensitive to LP treatment, which is consistent with our previous research in which Bogao was a P-sensitive genotype, while NN94156 was a P-tolerant genotype [30,32]. Furthermore, previous and our results reveals that all the mRNA, circular RNA and lncRNA, Bogao is more sensitive to LP stress than that of NN94156 [30,32].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2b and Fig. S1, the number of DE lncRNAs under LP stress in Bogao is more than that in NN94156, indicating that the Bogao is more sensitive to LP treatment, which is consistent with our previous research in which Bogao was a P-sensitive genotype, while NN94156 was a P-tolerant genotype [30,32]. Furthermore, previous and our results reveals that all the mRNA, circular RNA and lncRNA, Bogao is more sensitive to LP stress than that of NN94156 [30,32].…”
Section: Discussionsupporting
confidence: 90%
“…5, Fig. 6), which was supported by previous studies focusing LP in soybean [32,42]. Previous research showed that NtMYB12 acts as a phosphorus starvation response enhancement factor and regulates NtCHS and NtPT2 expression, which results in increased avonol and P accumulation and enhances tolerance to LP stress [43].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…K + deficiency affected root development in a wide range of plant species (Jia et al, 2008;Maathuis, 2009;Zhang et al, 2009;Hafsi et al, 2014;Guo et al, 2019). To study the potential miRNA-mediated mechanism in which plant responds to K + deficiency, we have selected and tested a total of 20 miRNAs that are associated with root development (Khan et al, 2011;Couzigou and Combier, 2016;Li and Zhang, 2016) and responses to nutrients (Maathuis, 2009;Kulcheski et al, 2015) including nitrogen and phosphorus deficiency (Bao et al, 2019;Filina et al, 2019;Yang et al, 2019;Asefpour Vakilian, 2020;Hou et al, 2020;Liu et al, 2020;Lv et al, 2020;Tiwari et al, 2020). These 20 miRNAs were miR160, miR164, miR165, miR166, miR167, miR169, miR171, miR172, miR390, miR393, miR396, miR847, miR857, miR156, miR162, miR319, miR395, miR778, miR399, and miR827.…”
Section: Rna Extraction Reverse Transcription and Gene Expression Amentioning
confidence: 99%